Success in banking examinations in nigeria volume 2 on monetary economics - Onuigbo Okonkwo (Aba, Nigeria 1992, 1992)
This volume contains 84 essay answers prepared in such concise manner that even the busiest candidates can profitably utilize the volumes for their examination purposes.
nmn 04/08/16
Loans
Keywords: Monetary economics - examination questions